Computational analysis of thrust generated by converging-diverging nozzle at different diverging angles - Bellary, Sayed Ahmed Imran; Dabir, Shahab Ahmed; Khan, Sher Afghan; Tamhane, Tushar; Shaikh, Javed Habib; Khan, Ambareen (Semarak Ilmu Publishing, 2025)
This study investigated the pressure rise characteristics of a shock train contained within a duct representative of a supersonic combustion ramjet (scramjet) isolator. The simulated isolator consisted of a constant area (25 mm by 30 mm) rectangular duct back-pressured by a triangular-shaped wedge with a vertex angle of 60 degrees. The CFD technique is used to investigate the performance of converging-diverging (CD) nozzles at different divergence angles ranging between 5° to13.5° with constant throat diameter and the isolator. The dimensions of the CD nozzle considered were 25.9 mm and 7.7 mm inlet and throat diameters, respectively, and nozzle pressure ratio (NPR) of 9. The study aims to isolate the shock wave inside the isolator so that fuel injection can be done at a supersonic Mach number. The 3D model is created on Inventor 2022 software, with a converging angle of 20° and a converging length of 25 mm. The results showed that the diverging angle is crucial in determining the back pressure and Mach number. An increase of diverging angle by 0.1° causes flow separation at the lip of the nozzle. Thus, the optimum diverging angle of 13.5° achieves maximum velocity for a given CD nozzle geometry at specific operating conditions.